High-resolution deep view microscopy of cells and tissues - Schneckenburger, Herbert; Richter, Verena; Gelléri, Márton; Schock, Florian; Hase, Johann von; Cremer, Christoph (Quantum electronics, 2020)
Methods, experimental setups and perspectives of three-dimensional deep view imaging microscopy of cell or tissue samples are reported. Preliminary biophysical and clinically relevant examples are presented.